Pengaruh Edukasi Pijat Common Cold Terhadap Pengetahuan Ibu dalam Mengurangi Batuk Pilek Pada Bayi - Reza Rahma Kumala; Kristina Maharani; Nella Vallen (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The common cold in infants is a frequent health problem that requires proper management to prevent potential complications such as pneumonia, bronchitis, sinusitis, laryngitis, and febrile seizures. Management strategies for the common cold can be carried out through pharmacological approaches, such as the administration of syrups and powders, and non-pharmacological approaches, including traditional methods like common cold massage. This study aims to analyze the effect of providing education about common cold massage on mothers’ knowledge in managing the common cold in infants. The research employed a quantitative method with a quasi-experimental design using a one-group pretest-posttest approach. The study population consisted of 40 mothers who had infants aged 4–12 months registered at the Gunungpati Health Center. A total sample of 36 respondents was obtained through simple random sampling. The research instrument was a structured knowledge questionnaire specifically developed to assess understanding of common cold massage techniques and their role in managing symptoms. Data analysis was conducted using the Wilcoxon signed-rank test to evaluate differences in knowledge levels before and after the educational intervention. The results showed a significant increase in mothers’ knowledge after receiving education, with a p-value of 0.000 (<0.05), indicating that the intervention was statistically significant. These findings highlight the importance of non-pharmacological educational programs, particularly common cold massage, as a complementary approach to infant health care. Implementing such education can empower mothers with practical skills to manage early symptoms and potentially reduce complications. It is recommended that further studies be conducted in different settings with more varied sociodemographic backgrounds to ensure broader applicability and to explore the integration of traditional massage education into community health programs.